1973
DOI: 10.1146/annurev.me.24.020173.001445
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Antibiotic Management in Surgery

Abstract: The general view of bacterial infection prevalent in medicine today is con cerned with the interaction of host and bacteria, rather than almost exclusively with bacteria as it was a few years ago following the introduction of antibiotic substances. This evolution, which promises to identify methods of infection pre vention, has found vigorous support in surgery because a primary problem in this discipline is the prevention of bacterial disease rather than the elimination of an established septic problem. Posts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

1975
1975
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 1 publication
0
11
0
1
Order By: Relevance
“…1999) although the increased numbers of leucocytes observed by 12 hours in our study suggest that the period of prophylatic therapy required is relatively short. Such a view has been supported by Burke (1973) and Rosin (1988).…”
Section: Discussionmentioning
confidence: 76%
“…1999) although the increased numbers of leucocytes observed by 12 hours in our study suggest that the period of prophylatic therapy required is relatively short. Such a view has been supported by Burke (1973) and Rosin (1988).…”
Section: Discussionmentioning
confidence: 76%
“…However, this behaviour is contrary to antibiotic prophylaxis guidelines, which state that tissue antibiotic levels should be high during the actual procedure (22). In fact, numerous authors have shown that prophylactic administration of antibiotics in the preoperative period can significantly reduce the postoperative wound infection rate (23)(24)(25)(26). Considering the duration of prophylaxis, the latter should be as short as possible as long as it is effective (21).…”
Section: Discussionmentioning
confidence: 99%
“…According to the consulted literature, when administering the antibiotic via the oral route, a single preoperative dose is sufficient. If the surgical intervention extends in time or tissue damage is considerable, another antibiotic dose can be administered at the equator of its therapeutic interval (22,26,27). In any case, antibiotic prophylaxis should not exceed 24 hours; extended administration does not reduce the infection rate, increases the risk of adverse drug reactions, and facilitates the emergence of bacterial resistances (22,26).…”
Section: Discussionmentioning
confidence: 99%
“…Postoperatively, the antibiotics can be given in the therapeutic dose of 500 mg every 6 hours. According to Burke,18 prophylactic antibiotic should be repeated every 3 hours during the operation. Prophylactic dosage interval of antibiotics is approximately one-half the usual therapeutic intervals.…”
Section: Jcdpmentioning
confidence: 99%